The efficacy of randomised controlled trials of guided and unguided self-help interventions for the prevention and treatment of eating disorders in young people: A systematic review and preliminary meta-analysis. (March 2023) - O'Mara, Madieson; Greene, Danyelle; Watson, Hunna; Shafran, Roz; Kenworthy, Isabel; Cresswell, Camilla; Egan, Sarah J.
Abstract: Background and objectives: Guided and unguided self-help prevention and treatment interventions for eating disorders delivered via traditional book format or internet delivery have been widely researched, but no reviews have focused specifically on young people. The aim of this systematic review and meta-analysis was to examine the efficacy of randomised controlled trials of self-help interventions for eating disorders in young people with a mean age between 13 and 24 years. Methods: A total of 8 intervention groups across 7 publications of self-help interventions which were prevention and treatment trials for eating disorders, were identified ( N  = 985 participants; mean pooled age = ∼19 years). Results: There was a significant very small effect (pooled g = −0.17) of self-help interventions at post-treatment which was non-significant at follow-up (pooled g = −0.14). No evidence of publication bias was found. Limitations: There were limitations of the review, including a lack of active treatment comparisons, a small number of trials included, and few studies included an age range. Conclusions: Results from this preliminary meta-analysis suggest very small but significant effects, however further studies are required to determine whether self-help approaches are effective for prevention and treatment of eating disorder symptoms in young people. Future meta-analyses should include a larger number of trials, and younger age range of children to examine the efficacy of self-help interventions for eating disorders in young people. Highlights: This review examined self-help for eating disorders in young people. 8 self-help interventions across 7 publications were identified. There was a significant effect (pooled g = −0.17) at post-treatment. Self-help intervention has a very small effect, more research is needed.